2017
DOI: 10.7448/ias.20.1.21422
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sex work involvement among transgender women in Jamaica: a cross-sectional study

Abstract: Introduction: Transgender women are disproportionately impacted by HIV. Transgender women involved in sex work may experience exacerbated violence, social exclusion, and HIV vulnerabilities, in comparison with non-sex work-involved transgender women. Scant research has investigated sex work among transgender women in the Caribbean, including Jamaica, where transgender women report pervasive violence. The study objective was to examine factors associated with sex work involvement among transgender women in Jama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
13
0
2
Order By: Relevance
“…The high probability of HIV-1 acquisition in transgender people is related to the legal and economic marginalisation that limit their employment options to sex work 7. The findings from Logie e t al 25 suggested that transgender women who are sex workers have a HIV-1 infection rates ninefold higher compared with transgender women not involved in sex work 25…”
Section: Discussionmentioning
confidence: 99%
“…The high probability of HIV-1 acquisition in transgender people is related to the legal and economic marginalisation that limit their employment options to sex work 7. The findings from Logie e t al 25 suggested that transgender women who are sex workers have a HIV-1 infection rates ninefold higher compared with transgender women not involved in sex work 25…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed 36.9% of female sex workers suffer from partner physical abuse and are associated with higher rates of mental health problems [59]. Higher rates of sex work were found in African female sex workers facing intimate partner violence [61,62]. In fact, a study conducted in India on female sex workers showed that many young married girls are beaten and abused.…”
Section: Physical Abusementioning
confidence: 99%
“…In fact, a study conducted in India on female sex workers showed that many young married girls are beaten and abused. This sexual and physical exploitation could be a motive for being a sex worker [61,62]. The emotional stress and the resulting mental health illnesses faced by women can consequently influence their choice of becoming a sex worker.…”
Section: Physical Abusementioning
confidence: 99%
“…There is no paucity of research articles on transgender women who work in the sex industry, and researchers have conducted studies around the globe and in countries such as China (Cai et al, ; Wang et al, ), Colombia (Bianchi et al, ), the Dominican Republic (Budhwani et al, ), India (Chakrapani, Newman, & Noronha, ), Jamaica (Logie et al, ), Malaysia (Nemoto, de Guzman, The, Iwamoto, & Trocki, ), Mexico (Infante, Sosa‐Rubi, & Cuadra, ), Pakistan (Collumbien et al, ; Usman, Khan, Bashir, Amjad, & Amjad, ); Peru (Degtyar et al, ), Portugal (Oliveira, ), South Africa (Samudzi & Mannell, ), Thailand, (Nemoto, de Guzman, et al, ), Turkey (Engin, ) and the United States (Nemoto, Operario, Keatley, Han, & Soma, , 2011; Sausa, Keatley, & Operario, , Wilson et al, , Hoffman, ). In much of this research, researchers focused on condomless sex between trans women who exchange sex for money with cisgender men, and how this high‐risk behavior contributed to high rates of HIV among transgender women in regions as diverse as China, Jamaica, Peru, and the Dominican Republic (e.g., Budhwani et al, ; Cai et al, ; Degtyar et al, ; Logie et al, ; Wang et al, ). Chakrapani et al, (2018) used a social exclusion framework that, without using the language of cissexism, examined the role of gender discrimination and marginalization as a motivation for trans women to trade sex.…”
Section: The Absence Of Transmasculine and Non‐binary People In Sex Wmentioning
confidence: 99%